2019
DOI: 10.17138/tgft(7)127-132
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and management of leucaena in Latin America

Abstract: Keynote paper presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.Leucaena leucocephala (leucaena) is native to Mexico and Central America and is currently naturalized in the majority of Latin American countries. Over the last 2 decades, considerable research and promotion of leucaena have been carried out in Colombia, Mexico, Cuba, Brazil, Paraguay and Argentina. Research focused on the agronomic and management options for feeding beef, dairy or dual-purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Animal productivity. Conference delegates confirmed that leucaena is a highly palatable, productive and profitable forage option used by beef producers in northern Australia (Buck et al 2019a; and by beef, dairy and goat producers in Colombia (Pachas et al 2019;Rivera et al 2019;Zapata Cadavid et al 2019;), Mexico (Ramírez-Avilés et al 2019), Paraguay (Glatzle et al 2019), Argentina (Radrizzani et al 2019a;, Indonesia (Dahlanuddin et al 2019;Waldron et al 2019), Myanmar (Aung 2019), India (Nimbkar 2019), Thailand (Nakamanee et al 2019a;, Venezuela (Escalante 2019) and Cuba (Ruiz et al 2019).…”
Section: Feeding and Management For Animal Productionmentioning
confidence: 95%
See 3 more Smart Citations
“…Animal productivity. Conference delegates confirmed that leucaena is a highly palatable, productive and profitable forage option used by beef producers in northern Australia (Buck et al 2019a; and by beef, dairy and goat producers in Colombia (Pachas et al 2019;Rivera et al 2019;Zapata Cadavid et al 2019;), Mexico (Ramírez-Avilés et al 2019), Paraguay (Glatzle et al 2019), Argentina (Radrizzani et al 2019a;, Indonesia (Dahlanuddin et al 2019;Waldron et al 2019), Myanmar (Aung 2019), India (Nimbkar 2019), Thailand (Nakamanee et al 2019a;, Venezuela (Escalante 2019) and Cuba (Ruiz et al 2019).…”
Section: Feeding and Management For Animal Productionmentioning
confidence: 95%
“…Leucaena and greenhouse gas implications. A subject area which provoked extensive discussion was the positive impact of leucaena plantings on reducing GHG emissions with papers by Tomkins et al (2019) from Australia, Chará et al (2019) from Colombia, Banegas et al (2019) from Argentina and Ramírez-Avilés et al (2019) from Mexico. Tomkins et al (2019) reported data that showed soil C in rangelands after 40 years was 17-30% higher under leucaena-grass pastures than under grass-only pastures.…”
Section: Leucaena and The Environmentmentioning
confidence: 99%
See 2 more Smart Citations